Gestão de Marcas País - O caso de Portugal - Sousa, Cláudio Manuel Gomes (2007)
The emergent globalization of the world economy, since the ending of the previous century, has contributed considerably to the increased competition between countries, regions and cities for the attraction of tourists, investments, qualified wok labour and, even, international events, as well as for the valorisation of its products (exportations), education institutions and culture. In a World where at times image and perceptions are believed to be more important than the reality itself, the development of Place Branding strategies are becoming one of the most important tools to the success and development of a country, region or city. In the last ten to fifteen years, countries like Scotland, New Zealand, Spain, Germany and USA, cities like Paris and New York, and regions like Arizona, Pyrenees or Silicon Valley have undertaken promotion strategies of their brands with the ultimate objective of value appropriation to themselves and to their citizens. With little more than seven years since its implementation, the promotion project of the Brand Portugal it s already a reality, even though it has been through less brightened moments, mainly because different paths have been employed in its short life. This case study has three objectives. First of all, wants to add to the increasingly knowledge of the main characteristics and tools used in Place Branding, so it can be used as a starting point for future investigations. Secondly, incorporating the case of the brand Portugal, this work is useful to the teaching of such subjects as Brand Management and Place Branding. Finally, has the objective to identify the major obstacles of the Portuguese project and to present some solutions for those barriers.